ANALISIS PENGARUH KEPUASAN KERJA DAN IKLIM ORGANISASI TERHADAP KEINGINAN KELUAR (INTENTION TO QUIT) DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Pada Perusahaan Perkebunan Kelapa Sawit TELADAN PRIMA GROUP) - Adhi Setyanto; Suharnomo Suharnomo; Sugiono Sugiono (JURNAL STUDI MANAJEMEN ORGANISASI, 2013)
This study aims to analyze the effect of job satisfaction, organisation climate and organizational commitment on intention to quite and to analyze the most affective variable on intention to quit. It is necessary to examine the factors affecting intention to quit so that management will be able to push turnover rate down. The company shall give a serious attention because a high turnover within a company can interrupt activities and productivities. High rate of turnover leads to adverse effect to an organization. Such problem is likely generating instability and uncertainty towards employment condition and human resources cost rise in forms of training invested to them, recruitment and newly built training programs. High turnover, in addition, also results in organizational ineffectiveness because it loses experienced employees as well as spends much times in training new, inexperienced employees. There are 165 respondents who are employees Teladan Prima Group for the samples and data analysis during the research is held by using SEM and AMOS 16.0 program. According to the analysis, it is concluded as the followings: job satisfaction has a positive effect on organizational commitment (CR = 3.111); organization climate has a positive on organizational commitment (CR = 4.258); organizational commitment has a negative effect on intention to quit (CR = -4.339); job satisfaction has a negative effect on intention to quit (CR = -2.165); and organizational commitment has a positive effect on intention to quit (CR = 1,319). Keyword : job satisfaction, organization climate, organizational commitment, and intention to quit